Space Flexibility : A Design Concept for Accomodating Spatial Invasion in Communal Flat - Joshua Gama Wastara; Arina Hayati; I Gusti Ngurah Antaryama (Institut Teknologi Sepuluh Nopember, 2020)
Housing needs are an urgent necessity for middle income residents in several areas in Surabaya. Thus, there are several dense settlements that were built illegally. The government provides the solution of simple rental flats (Rusunawa) as their substitute residence. Relocation of illegal settlement to rusunawa is often rejected by the inhabitant because oftentimes the design does not accommodate basic needs according to inhabitant’s perceptual and subjective view. Space invasion as a lifestyle expression of informal settlement is often overlooked when designing a simple, low-cost apartment buildings (Rusunawa). The purpose of this study is to propose a flexible architectural concept, based on observations of space invasion exploration gathered from field studies. This study is initiated from an exploratory thinking which drives the formation of the architectural design-based research to determine the design issue, hypothesis and design mapping based on the method of conceptual design. Literature and precedent studies are obtained to propose the first hypothesis that will be applied and explored through field research investigation. The field study is conducted at the riverbank’s settlement of Medokan Semampir Indah Tangkis Surabaya, which has a creative pattern and expression of space invasion. Our hypothesis states that spatial invasion activities are ways of expressing the lifestyle of people who live in riverbanks settlement. The Spatial invasion is expressed in domestic, social and economic activities. The results are then used as main idea or primary force for the concept design of collective residence, and to provide design criteria and parameters that suits to the needs and desires of the inhabitants.